2003
DOI: 10.2307/1543296
|View full text |Cite
|
Sign up to set email alerts
|

Possible Roles of Sulfur-Containing Amino Acids in a Chemoautotrophic Bacterium-Mollusc Symbiosis

Abstract: Invertebrate hosts of chemoautotrophic symbionts face the unique challenge of supplying their symbionts with hydrogen sulfide while avoiding its toxic effects. The sulfur-containing free amino acids taurine and thiotaurine may function in sulfide detoxification by serving as sulfur storage compounds or as transport compounds between symbiont and host. After sulfide exposure, both taurine and thiotaurine levels increased in the gill tissues of the symbiotic coastal bivalve Solemya velum. Inhibition of prokaryot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…Cycloheximide is widely used as an inhibitor of cytoplasmic protein synthesis in ectotherms including marine mollusks (Giuditta et al, 1968;Alkon et al, 1987;Fuery et al, 1998;Joyner and Peyer, 2003). In our preliminary studies, we tested different cycloheximide concentrations and found that concentrations between 75 and 750·mol·l -1 showed a similar and consistent degree of inhibition of cellular M O 2 (by 10-15%).…”
Section: Temperature-cadmium Interactions In Oyster Bioenergeticsmentioning
confidence: 88%
“…Cycloheximide is widely used as an inhibitor of cytoplasmic protein synthesis in ectotherms including marine mollusks (Giuditta et al, 1968;Alkon et al, 1987;Fuery et al, 1998;Joyner and Peyer, 2003). In our preliminary studies, we tested different cycloheximide concentrations and found that concentrations between 75 and 750·mol·l -1 showed a similar and consistent degree of inhibition of cellular M O 2 (by 10-15%).…”
Section: Temperature-cadmium Interactions In Oyster Bioenergeticsmentioning
confidence: 88%
“…In contrast all sulfur compounds in the leaves originated of a mixture of reoxidised sulfide and bulk pore water sulfate (Hasler-Sheetal, 2014). Also S-containing amino acids, such as taurine and thiotaurine, have been suggested as storage compounds of toxic sulfide in chemoautotrophic bacteria experiencing high sulfide concentrations (Joyner et al, 2003), a similar mechanism is possible in the seagrasses, but further studies are needed.…”
Section: Fate Of Sulfide Inside Seagrassesmentioning
confidence: 99%
“…However, HT can also react with sulfide directly, forming thiotaurine (ThT) in vitro (Cavallini et al, 1963). If this reaction occurs in vivo, it would scavenge free sulfide and might, therefore, reduce sulfide toxicity by acting as a sulfide 'buffer' (Alberic and Boulegue, 1990;Brand et al, 2007;Joyner et al, 2003;Pruski and Fiala-Medioni, 2003;Rosenberg et al, 2006). In sulfide-exposed animals that lack sulfide-oxidizing endosymbionts, the resulting ThT may be enzymatically recycled back to HT, thereby releasing sulfide at a rate that allows detoxification through other mechanisms (Rosenberg et al, 2006).…”
Section: Introductionmentioning
confidence: 99%